PERLINDUNGAN HUKUM BAGI TENAGA KERJA PEREMPUAN HAMIL YANG MENGALAMI PHK - Manus, Yustus Hendrik; Ahmad, Muh. Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to examine legal arrangements regarding legal protection of the rights of pregnant female workers who have experienced termination of employment based on the Job Creation Law and to find out legal remedies that can be taken by pregnant female workers who have experienced layoffs to fulfill their rights by employers. . This study uses a normative legal research method, namely an approach to the problem in terms of the applicable laws and regulations, especially regarding employment. Data collection techniques through library research or library research, namely collecting primary legal materials and secondary legal materials. The results of the research, namely legal protection for the rights of workers who have experienced layoffs, have been regulated in Article 156 of Law Number 11 of 2020 concerning Job Creation, amendments to Law Number 13 of 2003, including: Maternity leave rights, severance pay, long service reward, Rights Substitute Money. Legal remedies that can be taken by workers who experience layoffs as a result of not fulfilling their rights by employers, namely by seeking settlements outside the Industrial Relations Court route starting from bipartite settlement, then the mediation or conciliation stages. While the settlement of disputes through the Industrial Relations Court, relates to decisions issued by the Industrial Relations Court